First Report of Zonate Leaf Spot in Sorghum Caused by Microdochium sorghi in Uruguay - Stewart, Silvina; Rodriguez Alonzo, Marcelo Julián; Mattos, Natalia; Abreo, Eduardo (Agrociencia Uruguay, 2019)
Sorghum leaves with concentric lesions, alternating purple to red and beige to cinnamon, were observed for the first time in January 2017. The same symptoms were observed later in 29 % of sorghum cultivars in official Evaluación Nacional de Cultivares INASE-INIA trials. The pathogen was identified as Microdochium sorghi (syn. Gloeocercospora sorghi) once pathogenicity trials, morphological and molecular descriptions were done. This is the first report of this pathogen affecting sorghum in Uruguay.